Lantamal XII Pontianak strategy in empowering maritime potential in the region to strengthen the total people's defense system - Mokhamad Subur; I Wayan Midhio; Edy Sulistyadi (Strategi Perang Semesta, 2022)
In the regional dimension, West Kalimantan is divided into three dimensions of the territory, namely coastal and island areas, inland areas and border areas between countries. It has a long coastline to the north bordering Malaysia. Based on its geographical location, one-third of West Kalimantan is along the coast and islands facing The Indonesian Archipelago Sea Lane (ALKI I). In accordance with the policy of the President of the Republic of Indonesia regarding the transfer of the New National Capital (IKN) to Kutai Kertanegara Regency precisely in Penajam Pasir Utara. This will have implications for the change of the Indonesian Center of Gravity (CoG) which is also moving from Jakarta to the new IKN. With such conditions in the geographical constellation of national resources, the West Kalimantan region has the potential for security disturbances that can occur in and or by sea. The Main Base of the Indonesian Navy XII Pontianak as one of the defense instruments, has the task to secure and maintain all forms of threats that arise. For this reason, by looking at the current situation of strategic environmental development, the right strategy is needed by empowering all maritime potential in the West Kalimantan region as a national resource to project power from sea to land in order to strengthen the Total People's Defense System (Sishanrata).